Development of water repellent, non-friable tannin-furanic-fatty acids biofoams - Azadeh, Elham; Abdullah, Ummi Hani; Md Ali, Nurul Basirah; Pizzi, Antonio; Gerardin-Charbonnier, Christine; Gerardin, Philippe; Samiun, Wan Sarah; Ashari, Siti Efliza (MDPI, 2022)
Tannin-furanic foams were prepared with a good yield using the addition of relatively small proportions of a polyflavonoid tannin extract esterified with either palmitic acid, oleic acid, or lauric acid by its reaction with palmitoyl chloride, oleyl chloride, or lauryl chloride. FTIR analysis allowed us to ascertain the esterification of the tannin, and MALDI-TOF analysis allowed us to identify a number of multi-esterified flavonoid oligomers as well as some linked to residual carbohydrates related to the equally esterified tannin. These foams presented a markedly decreased surface friability or no friability at all, and at densities lower than the standard foam they were compared to. Equally, these experimental foams presented a much-improved water repellence, as indicated by their initial wetting angle, its small variation over time, and its stabilization at a high wetting angle value, while the wetting angle of the standard foam control went to zero very rapidly. This conclusion was supported by the calculation of the total surface energy of their surfaces as well as of their dispersive and polar components.